(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The author briefly presented the economic and social situation in the countries of the Horn of Africa: Djibouti, Ethiopia, Eritrea and Somalia and showed how she reacted to newcomers from these countries Saudi Arabia.